2012
DOI: 10.3892/ol.2012.582
|View full text |Cite
|
Sign up to set email alerts
|

KiSS1/GPR54 and estrogen-related gene expression profiles in primary breast cancer

Abstract: Abstract. The estrogen receptor α (ERα)-mediated pathway plays a critical role in breast cancer development and progression. KiSS1 was previously described as a metastasis suppressor gene in certain carcinomas. However, the role of KiSS1/GPR54 in breast cancer remains controversial. Whether the function of the KiSS1/GPR54 system depends on estrogen signaling in the breast cancer cell remains to be determined. This study aimed to determine the expression profiles of the KiSS1/GPR54, ERα, ERβ, aromatase and cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
1
6
4
1
Order By: Relevance
“…In contrast to this study, Jarzabek and others reported that ER-positive tumors exhibited higher KISS1 and KISS1R levels than ER-negative tumors50. This study also revealed that KISS1R expression is negatively associated with HER2 status in breast cancer50. Thus the expression profile and roles of KISS1 and KISS1R in breast cancer has been difficult to discern and this might simply reflect the great heterogeneity among breast tissue, in addition to the fact that mRNA levels may not necessarily correlate to protein levels.…”
Section: Regulation Of Kiss1 and Kiss1r Expression By Estrogen In Brecontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to this study, Jarzabek and others reported that ER-positive tumors exhibited higher KISS1 and KISS1R levels than ER-negative tumors50. This study also revealed that KISS1R expression is negatively associated with HER2 status in breast cancer50. Thus the expression profile and roles of KISS1 and KISS1R in breast cancer has been difficult to discern and this might simply reflect the great heterogeneity among breast tissue, in addition to the fact that mRNA levels may not necessarily correlate to protein levels.…”
Section: Regulation Of Kiss1 and Kiss1r Expression By Estrogen In Brecontrasting
confidence: 99%
“…They reported that KISS1 mRNA levels were high in breast tumors, compared to normal mammary tissue, whereas KISS1R mRNA levels were high in invasive tumors compared to normal tissue78. In contrast to this study, Jarzabek and others reported that ER-positive tumors exhibited higher KISS1 and KISS1R levels than ER-negative tumors50. This study also revealed that KISS1R expression is negatively associated with HER2 status in breast cancer50.…”
Section: Regulation Of Kiss1 and Kiss1r Expression By Estrogen In Brecontrasting
confidence: 81%
“… 19 Some studies reveal that KiSS1 mRNA expression is also markedly reduced in tissues of breast cancer, 20 while other ones show that KiSS1 is highly expressed in estrogen receptor (ER)-positive breast tumors compared to the ER-negative tumors. 21 KiSS1 expression levels are found to be decreased in OS cell lines with increasing aggressiveness, while increases in human OS tissues and correlates with the metastasis of OS. 22 Differently from the study of Wang et al, 22 we found in the present study that KiSS1 was proved to be decreased in the nucleus and cytoplasm of human OS tissues compared to the ANCT, suggesting that loss of KiSS1 expression might be involved in the development of OS.…”
Section: Discussionmentioning
confidence: 90%
“…They showed that in ERα-positive primary tumors, KiSS-1 levels are lower than ERα-negative tumors ( 22 , 23 ). In contrast, Jarzabek and colleagues demonstrated that ERα-positive breast tumors express higher levels of both KiSS-1 and KiSS-1R than ERα-negative tumors ( 24 ).…”
Section: Kiss-1 As a Metastasis Suppressor Genementioning
confidence: 97%